GENDER CULTURE AND EDUCATION: INTEGRATION PROBLEMS AND SOLUTIONS - Adolat Ziyotova (Bright Mind Publishing, 2025)
This paper explores the integration of gender culture into the educational system, focusing on the challenges and potential solutions associated with this process. As modern education increasingly embraces inclusive and equitable approaches, understanding how gender values are reflected and implemented in curricula, teaching practices, and institutional policies has become a critical area of study. The research highlights key obstacles to effective gender mainstreaming in education, including persistent stereotypes, lack of gender-sensitive training among educators, and insufficient institutional support. At the same time, the study proposes practical strategies to address these issues, such as reforming educational content, enhancing teacher competencies in gender awareness, and promoting a more inclusive academic environment. The analysis emphasizes that fostering gender culture in education is essential for building a just, respectful, and progressive society.
Keywords: Gender culture, education system, gender equality, integration challenges, inclusive education, teaching practices, curriculum reform, gender sensitivity, teacher training, educational policy